Hybridizing Due Diligence: Governing Human Rights Risks in Nigeria's Informal Economy Through Ground-Up Governance - Muhammad jibril, Abubakar; Rabiu Abdulmudallib Bello (Center for Law and Responsible Business Studies, 2025)
This article discusses how human rights due diligence can be operationalized in Nigeria's large informal economy using a hybrid governance approach. Applying a normative legal approach, we examine Nigeria's statute law, policy, and institutional stipulations (e.g., the 1999 Constitution and National Human Rights Commission Act), alongside recent policy documents like the National Action Plan (NAP) on Business and Human Rights (adopted in 2023) and attendant human rights strategies. We evaluate shortcomings of the existing top-down strategy, observing that formal business regulations and labour laws have the effect of excluding unregistered businesses and family enterprises, and outline the specific dilemmas of informal players. Pointing to examples such as the FIWON cooperative of street-level traders and local savings plans, we turn to